PENGARUH METODE LATIHAN DRILL TERHADAP TEKNIK PASING BAWAH BOLA VOLI PADA SISWA EKSTRAKURIKULER SMPN 2 PANGKALAN - Mar'atul Afifah Afifah; Rizki Aminudin; Abduloh Abduloh (Jurnal Speed (Sport, Physical Education, Empowerment), 2020)
The purpose of this study was to determine the effect of student training skills on the basic technique of volleyball bottom fitting through the drill training method on extracurricular students at SMPN 2 Pangkalan, the problem of this research is that when doing pasing under the arm, the elbow is bent and the ball is not directed or on target. and the training method is less effective, as for the benefits that can be taken from this research is that it can add to the study or contribute ideas for the renewal of the training program which continues to develop in accordance with the needs of volleyball extracurricular development and can improve the quality of the training. The population sampled in this study were 26 extracurricular students at SMPN 1 Pangkalan while the sample used in this study were 13 female students who were taken by random sampling. The approach used in the study. This is a quantitative approach and a type of experimental research with the design of `` The One Group Pre test Post Test '' The instrument used in this study is an indicator of the pretest and posttest assessment, the results of the study show that there is a significant effect of the drill training method on increasing the ability to pass. under volleyball extracurricular students of SMPN 2 Pangkalan with a t-value of 3.91> t-table 1.771 and a significance value of 0.023 <0.05 and an increase in the percentage of 72.25%.